THE ECOSUFISM DIMENSION OF FARMER GROUP MEMBERS BY MAINTAINING THE RELATIONSHIP BETWEEN HUMANS AND NATURE - Mohammad Rafli Aminullah; Zamzami Sabiq; Aminudin (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2024)
The crisis in small-scale sectors like agriculture has become pervasive, as farmers directly engaged with the agricultural ecosystem frequently neglect the necessary balance and harmony. The once harmonious interaction between humans and nature is now neglected due to the persistent symptoms of unrestrained anthropocentrism. This study aims to elucidate how ecosufism, perceived as a solution, is enacted by members of a farming collective, reflecting the diverse features of their local expertise. This study employs a descriptive qualitative research methodology, utilizing the theoretical framework of Imam Al-Ghazali, supplemented with the theories proposed by Seyyed Hossein Nasr and Suwito NS. The conducted research revealed that members of the farmer group exhibit ecosufism dimensions characterized by spirituality, environmental ethics, holistic awareness, and sustainable practices, which include fostering positive relationships with nature, complemented by tangible actions and informed by local wisdom.